Performance evaluation of masonry grout containing high volume of palm oil industry by-products - Nayaka, Ramappa Ramesh; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Yusoff, Sumiani; Ganasan, Reventheran (Elsevier, 2019)
The rapid depletion of natural resources has led to the need to develop sustainable practices and material in various applications. One such sustainable practice is to divert the waste generated in the palm oil industry into production of building materials. In this study, palm oil clinker (POC) is used to replace cement and coarse aggregate. The POC chunks are crushed to be used as coarse aggregate and further ground to produce POC powder (POCP) to be used as a binder. The physical properties, chemical composition and scanning electronic microscopic studies were conducted to check the feasibility of substitution of up to 50% POCP as binder and up to 100% POC as coarse aggregate. Density, ultrsonic pulse velocity(UPV), compressive strength for air & water curing, flexural, tensile strength, modulus of elasticity in water cured regimes and structural efficiency were evaluated for the samples. Carbon footprint, cost effieciency and energy savings were also evaluated to understand the contribution of POC to sustainability. The results revealed that the ideal mixture of GPP (30% POCP & 50% POC) masonry grout achieved 79% of compressive strength, a 83% of flexural strength, 85% of tensile strength and about 85.5% of modulus elasticity, as compared to control masonry grout. Carbon emissions of GPP was reduced by 21% and 14.60% cost reduction was established, in addition, appreciable energy savings was notified. The study showed that that utilisation of POC as eco-friendly material in masonry grout is highly recommended based on performance and can provide a route to sustanable practices in the building industry. © 2019 Elsevier Ltd